(3GdegPHs - (3GdWQGHdSj, CHh GdbGSe ` GHf GdHQGL, YHO GdYRjR Hf HMQ Hf YHO GdYRjR, J (B481 (3g`s ((3MSf Hf CHj eYUhe GdchcOjs)
(3ChdgG (B:s
(3HGH GdEbQGQ EPG CbQ GdMQ GdHGdZ GdcGed GdYGbd(B...(3cGf EbQGQg eGVjG(B...s
(3BNQgG (B:s
(3hcPdc dh JRhL eSde cJGHjI Ke WdbgG KdGKG(B...(3Je GdLRA GdKGdKs
(3JHUQI GdeDda (B:s
(3SeGg UGMH GdCYdGe(B: (3YHO GdYRjR Hf HMQ(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B4(3,U(B15s
(3eYLe GdeDdajf(B:(3L(B2(3,U(B169s
(3GdPQjYI(B:(3L(B23(3,U(B181(3,Qbe(B9038s
Keywords: (3abg GdePGgH GdCNQis